Efficiency analysis of swimmers` start using starting block with adjustable raised foot in competitions - Petryaev, A. V. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
IINTRODUCTION: The aim of this work was to determine the influence of the use of starting block with adjustable raised foot on the start efficiency. METHODS: In this research 16 international level sportsmen took part. The specialization of swimmers was distances of 50, 100 and 200 meters in butterfly and freestyle. Comparative data was obtained in the sportsmen`s competitive activity analysis at the international competitions of the World cup lap in Moscow and the European championship in Istanbul on the short water during one month in the November and December 2009. Also finalists` results on the first 15-meters section of the distances in both competitions were analyzed. On the first start in Moscow the usual starting blocks without adjustable raised foot were used, on the second start in Istanbul the same swimmers used the starting block with adjustable raised foot. Athletes were in the same swim suits, that means that the constituent of the frontal component of active drag depending on the swim suit type was constant. In the research digital video cameras were used, the beginning of the start was synchronized with the flash and it was taken into account in the video file processing. The time fixation was made by the swimmer`s head while they passed the 15-meters of the start section. RESULTS: The data analysis of finalists of the World cup lap and the European championship showed a high correlation of the time of passing the 15-meters start section and the sport result: on the distance of 50 meters (men and women) r=-0,65-0,70; on the distance of 100 meters r=-0,60-0,65; on the distance of 200 meters r=-0,50-0,55; on the distance of 400 meters r=-0,25-0,30. The average time of start section passing using the starting block with adjustable raised foot decreased on the distance of 50 meters by 2,25%* and the sport result time decreased by 0,63%*; on the distance of 100 meters - by 2,20%* and 1,34%*, respectively; on the distance of 200 meters - by 2,22%* and 1,72%*, respectively (* p>0,01). DISCUSSION: Swimmers of high qualification have the capability to make stably the start section of the distance. Considering that the swimmers participated in both competitions in the same typical swim suits and the external conditions did not change the start section result improvements can be explained with the influence of the use of starting block with adjustable raised foot.